Ruwatan dreadlocks ritual: branding Dieng as a cultural tourism destination in Wonosobo - Mahmudi, Marwan; Mansur, Suraya; Amrullah, Haekal Fajri (Faculty of Communications Science, Dr. Soetomo University, 2025)
Identity is entirely a social construction and cannot exist outside cultural representation and acculturation because identity is within the social and cultural environment. In the context of tradition, identity is related to the position and social position of the community. Dreadlocked children are believed to have more daring personalities than humans who are destined to have normal hair. This phenomenon is not limited to dreadlocks who live in Dieng. Several cases were also found in individuals who had direct descendants of the Dieng population, even though they were domiciled outside the Dieng area. This research used Cultural Identity Theory and city branding. What is their social identity? How does the ritual transformation of dreadlocks contribute to the activation of Dieng's brand as a tourist destination? This study employed the constructivism paradigm and analysed systematically meaningful acts socially, especially on the dreadlocks in Dieng, Central Java. The methodological approach is qualitative. The informants are six parents, public figures, and officials. The result shown: For the people of Dieng Plateau, the number of dreadlocked children correlates with people's welfare. The greater the number of dreadlocked children, the better their welfare. The misunderstanding is that the dreadlocks are special, smart, hyperactive because the dreadlocks are guarded by supernatural beings. Related to tourist destinations, the local government uses it as part of a cultural tourism destination that is economical in purpose.